A study of abrasive water jet machining process on glass/epoxy composite laminate - M. A., Amir; Khan, Ahsan Ali (Elsevier, 2009)
Surface roughness (Ra) and kerf taper ratio (TR) characteristics of an abrasive water jet machined surfaces of glass/epoxy composite laminate were studied. Taguchi’s design of experiments and analysis of variance were used to determine the effect of machining parameters on Ra and TR. Hydraulic pressure and type of abrasive materials were considered as the most significant control factor in influencing Ra and TR, respectively. Due to hardness of aluminium oxide type of abrasive materials, it performs better than garnet in terms of both machining characteristics. Increasing the hydraulic pressure and abrasive mass flow rate may result in a better machining performance for both criteria. Meanwhile, decreasing the standoff distance and traverse rate may improve both criteria of machining performance. Cutting orientation does not influence the machining performance in both cases. So, it was confirmed that increasing the kinetic energy of abrasive water jet machining (AWJM) process may produce a better quality of cuts.